96 Adult Nasal Chondromesenchymal Hamartoma: A Rare and Benign Tumour with Aggressive Malignant Transformation. (28th February 2022) - Collins, R.; Lafford, G.; Meghji, S.; Burrows, S.
Abstract: Nasal chondromesenchymal hamartoma (NCMH) is an extremely rare benign tumour of the nasal cavity predominantly described in infants. To date, a total of 59 cases have been described. We report a case involving a 48-year-old female who had been diagnosed with NCMH a year earlier and now represented with a short history of progressive nasal blockage, recurrent epistaxis, and orbital apex syndrome. Histopathology was suggestive of malignant transformation into sinonasal sarcoma. However, following multi-disciplinary team (MDT) discussions including a second and third opinion from external departments, the histological diagnosis was revised to 'NCMH with bizarre stromal cells. Despite this, clinically the lesion demonstrated malignant features with rapid, invasive growth and was treated with palliative radiotherapy. The patient later developed radiological signs of lung and liver metastases and subsequent pulmonary emboli. Shortly after this she passed away. This case is unique in its diagnostic challenge, with ambiguous histopathological findings, and highlights the importance of an MDT approach when managing complex sinonasal tumours.